2007
DOI: 10.1016/j.worlddev.2006.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Victimization: The Case of Mozambique

Abstract: JACINTO CHICONELA Ministry of Planning and Development (MPD), MozambiqueSummary. -This paper analyzes how different economic characteristics at the individual, household and community level affect the risk of victimization, controlling for the impact of (non-economic) sociological factors. We use a nation wide household survey from Mozambique and show that the probability of being victimized is increasing in income, but at a diminishing rate. At the same time, poorer households are vulnerable. While less at ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 20 publications
3
30
0
1
Order By: Relevance
“…In fact, there is a positive and significant relationship between being male and exposure to thefts (including larcenies and burglaries). This is in accordance with what is found by Gomes and Paz (2005) in the city of São Paulo and the result of Barslund et al (2007) in Mozambique, where males are found to have a higher probability of victimization of any type of crime than a female.…”
Section: Results For Crime Victimizationsupporting
confidence: 92%
See 4 more Smart Citations
“…In fact, there is a positive and significant relationship between being male and exposure to thefts (including larcenies and burglaries). This is in accordance with what is found by Gomes and Paz (2005) in the city of São Paulo and the result of Barslund et al (2007) in Mozambique, where males are found to have a higher probability of victimization of any type of crime than a female.…”
Section: Results For Crime Victimizationsupporting
confidence: 92%
“…In Africa, some recent works have addressed the issue. We have, for instance, a research in Mozambique (Barslund et al 2007) and another one in South Africa (Powdthavee 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations